Піраміда показників енергетичної ефективності на рівні підприємства - Костін, Ю. Д.; Пустовий, О. Ю. (ХНУРЭ, 2015)
To increase the accuracy of the energy efficiency estimation the principe of hierarchy had been proposed - consideration of energy efficiency indicators separately at different levels - at the micro level, at industry sector / subsector, individual enterprise, type of activity, and therefore a pyramid energy efficiency indicators of industrial enterprises was built. Such structure is broken down at the level of processes, equipment , structural units and enterprises as a whole. Also the aggregated energy efficiency indexes at different levels of pyramide was formed.
Keywords: показники енергетичної ефективності; енергетична ефективність підприємства